2004
DOI: 10.1111/j.1099-1123.2004.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit Fees and Market Segmentation – Further Evidence on How Client Size Matters within the Context of Audit Fee Models

Abstract: The purpose of this paper is to examine the audit fee premium to the Big 6 brand in the small and large client segments of the market for audit services. We use a sample of Australian fee data for the five‐year period 1995 to 1999. We find evidence of price premiums to Big 6 auditors in the small client segment. We do not find evidence of fee premiums in the large client segment. We also present evidence that audit fees are not linearly related to client size as is typically assumed in audit fee models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 27 publications
5
46
0
13
Order By: Relevance
“…The size of auditee has a direct impact on the auditors' work, and the time spent in the auditing process. Larger clients require more audit services than smaller clients, more time needed; hence we would expect that these large clients pay higher fees per dollar of size relative to smaller clients in the industry (Palmrose, 1986;Carson, Fargher, Simon & Taylor, 2004). Hence, there is a positive relationship between audit fees and auditee size.…”
Section: Client Size (Auditee Size)mentioning
confidence: 99%
See 2 more Smart Citations
“…The size of auditee has a direct impact on the auditors' work, and the time spent in the auditing process. Larger clients require more audit services than smaller clients, more time needed; hence we would expect that these large clients pay higher fees per dollar of size relative to smaller clients in the industry (Palmrose, 1986;Carson, Fargher, Simon & Taylor, 2004). Hence, there is a positive relationship between audit fees and auditee size.…”
Section: Client Size (Auditee Size)mentioning
confidence: 99%
“…Hence, there is a positive relationship between audit fees and auditee size. (Simunic, 1980;Low et al,1990;Chan et al, 1993;Carson et al, 2004).…”
Section: Client Size (Auditee Size)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors can be used to reflect the complexity of the company. Previous studies (Simunic, 1980;Francis & Simon, 1987;Joshi & Bastaki, 2000;Carson et al, 2004;Gonthier-Besacier & Schatt, 2007;Thinggaard and Kiertzner, 2008) included several measures of complexity such as, firstly, physical complexity as measured by number and location of operating units, and the diversification of product lines. Secondly, legal complexity as measured by number of the company's subsidiaries and affiliates, and number of countries in which the company operates.…”
Section: Auditee Complexitymentioning
confidence: 99%
“…Consequently, in researches on pricing of audit service determinants, both of the countries have been focused on: US (Taylor & Simon, 1999;Bedard & Johnstone, 2010;Callaghan et al, 2008) and the UK (Moizer, 1997;Pong, 2004). In addition, scholars have also taken companies of Australia (Carson et al, 2004;Carson & Fargher, 2006), France (Gonthier-Besacier & Schatt, 2007), India Bangladeshi, and Pakistan (Ahmed and Goyal, 2005), Danmark (Thinggaard and Kiertzner, 2008), Bahrain (Joshi and Bastaki, 2000), Kuwait (Meshari, 2008) into consideration. In most of the mentioned studies, relationships between external audit fees and some factors are usually found.…”
Section: Introductionmentioning
confidence: 99%